Hydrophobically Associating Polymers Dissolved in Seawater for Enhanced Oil Recovery of Bohai Offshore Oilfields - Fei Yi; Bo Huang; Chengsheng Wang; Xiaoxu Tang; Xiujun Wang; Quangang Liu; Yanhui Su; Shijia Chen; Xiaoyan Wu; Bin Chen; Jing Zhang; Dianguo Wu; et al. (Molecules, 2022)
As compared to China’s overall oil reserves, the reserve share of offshore oilfields is rather significant. However, offshore oilfield circumstances for enhanced oil recovery (EOR) include not just severe temperatures and salinity, but also restricted space on offshore platforms. This harsh oil production environment requires polymers with relatively strong salt resistance, solubility, thickening ability, rapid, superior injection capabilities, and anti-shearing ability. As a result, research into polymers with high viscosity and quick solubility is recognized as critical to meeting the criteria of polymer flooding in offshore oil reservoirs. For the above purposes, a novel hydrophobically associating polymer (HAP) was prepared to be used for polymer flooding of Bohai offshore oilfields. The synthetic procedure was free radical polymerization in aqueous solutions starting at 0 °C, using acrylamide (AM), acrylic acid (AA), 2-acrylamido-2-methylpropane sulfonic acid (AMPS), and poly(ethylene glycol) octadecyl methacrylate (POM) as comonomers. It was discovered that under ideal conditions, the molecular weight of HAP exceeds 2.1 × 107 g⋅mol−1. In a simulated reservoir environment, HAP has substantially greater solubility, thickening property, and salt resistance than conventional polyacrylamide (HPAM), with equivalent molecular weight. Finally, the injectivity and propagation of the two polymers in porous media were investigated. Compared with HPAM, which has a similar molecular weight, HAP solution with the concentration of 0.175% had a much better oil displacement effect in the porous medium, which can enhance oil recovery by 8.8%. These discoveries have the potential to pave the way for chemical EOR in offshore oilfields.